Variation of voids and inter-layer shear strength of advanced polymer-matrix composites at different pressures with high-pressure microwave. (September 2019) - Chen, Xiaoping; Zhan, Lihua; Pu, Yongwei; Huang, Minghui; Chen, Xiwen; Guan, Chenglong; Wu, Xintong; He, Jiayang
Due to its rapid and volumetric heating capabilities, microwave heating has been conceived as an alternative cost-effective route for curing advanced polymer-matrix composites. Different curing pressures were applied to the pre-impregnated laminates of advanced polymer-matrix composites in a given high-pressure microwave curing process. The variation of voids' shapes in the advanced polymer-matrix composites was revealed, and the shear failure mechanism of advanced polymer-matrix composites with different porosity was analyzed. During the shear failure process of the advanced polymer-matrix composites, sounds ceaselessly occur. The experiment results of the optical digital microscopy, the scanning electron microscope, and the inter-laminar shear properties test showed that in high-pressure microwave curing process, pressure was not only the main factor that affects the porosity and the mechanical properties but also influences the bonding strength of the resin and the carbon fiber interface significantly. There is a threshold value for the effect of curing pressure on porosity and inter-laminar shear strength of advanced polymer-matrix composites. The internal relationship among porosity, inter-laminar shear strength, and curing pressure of advanced polymer-matrix composites could be summarized as a piecewise power function.